Pengaruh Oleamida Terhadap Karakteristik Pematangan Karet Alam Terisi Silika - Surya, Indra; Philbert (Talenta Publisher (Universitas Sumatera Utara), 2021)
The purpose of this study was as a feasibility study of the utilization of oleamide as a new additive for natural rubber (NR) filled with silica using the semi-efficient vulcanization system. Silica fillers used as much as 30 parts per hundred parts rubber (phr). Oleamide was obtained from the synthesis of oleic acid with urea. Oleamide was inserted into the silica filled NR compounds with the varied composition of 0.0 phr; 2.0 phr; 4.0 phr; 6.0 phr, and 8.0 phr. The influence of oleamide on the curing characteristic of the silica filled NR compounds was observed. It was obtained that the oleamide functions as a curative and also a plasticizer. The greater the levels of oleamide added, the shorter the scorch time and optimum curing time were. Oleamide also decreased the minimum torque with addition up to 8.0 phr. The greater the levels of oleamide was, the lower the minimum torque was. Oleamide also increased the maximum torque and torque difference of the silica-filled NR composites at the addition of 2.0 phr. The 2.0 phr was the optimum composition of the oleamide.